Bahasa Inggris - Alhaerani Sianti Sulhan; Insih Wilujeng; Zuhdan Kun Prasetyo (Postgraduate, University of Mataram, 2023)
This study aims to determine the improving in students’ critical thinking skills through problem based learning e-modules on momentum and impuls material. The method used in this study was a pre-experimental design with a one-group pretest-posttest design. The research sample was X MIPA SMAN 1 Depok, totalling 35 students. Collecting data on critical thinking skills using essay tests. The research data was collected from the pretest and posttest of critical thinking skills on momentum and impuls material. The results showed the difference in pretest and posttest averages for each indicator of critical thinking skills, namely the indicator of formulating problems 6.57, evaluating logical arguments 5.83, making conclusions 5.19, and analyzing facts 5.09. Furthermore, the critical thinking skills of students experienced an increase after learning activities were carried out using problem-based learning e-module momentum and impuls with an N-gain value obtained of 51.41% in the medium category. Problem based learning can improve students’ critical thinking skills.